Síndrome de hiperémesis por cannabinoides: caso clínico - Benavides A., Daniela; Valle S., Daniela; Ibáñez P., Carlos (Revista Hospital Clínico Universidad de Chile, 2019)
Background. The cannabinoid hyperemesis syndrome (CHS) was first described in 2004. It is considered as a functional gastrointestinal syndrome characterized by the presence of nausea, severe and cyclic morning vomiting, epigastric abdominal pain, hot water bathing for symptom relief, in patients that use cannabis regularly and has a resolution of the syndrome after cessation of cannabis consumption. Clinical Case. Report of a 29 year old male, with daily consumption of cannabis, with history of intense epigastric abdominal pain and recurrent vomiting that partially responded to the use of antispasmodics. After 4 visits to the emergency department he was hospitalized for study and treatment. Laboratory and image exploration are carried out without positive results for organic disease. Therefore, a functional gastrointestinal syndrome is thought, and a cannabinoid hyperemesis syndrome was suspected. A psychiatric evaluation is carried out, diagnosing a cannabis use disorder. Discussion and conclusion. CHS is a syndrome that has been described recently and is not usually considered as a differential diagnosis for patients with hyperemesis. However, the current high prevalence of cannabis consumption, will probably lead to a more frequent presentation of the syndrome at different health providers. Therefore, it is important to diffuse and update the knowledge about this syndrome to recognize it and develop a timely treatment, avoiding medical complications from invasive exploratory methods and the use of unnecessary resources.